An evaluation of the collections of selected university of the Philippines Diliman Libraries on christian and Islamic sacred scriptures - Roque, Nicolae Ignatius I. (Institute of Library Science, University of the Philippines Diliman, 2002)
The two major religions in the Philippines are Christianity and Islam. The sacred scriptures of the two are the Bible and the Koran, respectively. This study evaluated the adequacy of the collections of these two sacred books and related materials in selected libraries in the University of the Philippines (UP) Diliman in terms of quantity, quality, availability and accessibility in relation to user demand. The libraries studied were three sub-units within the Main Library - the Social Science Section, General Reference Section and the Filipiniana Section - and the Institute of Islamic Studies (IIS) Library. User demand was defined by the collections' clientele, whether active - those who have already used the materials under study - or potential - those who have not yet used the materials but have expressed a desire to do so. This is determined through two means: survey and documentary analysis, which shows book use.